Harapan dan Kenyataan Pelaksanaan Pembelajaran di Institusi Pasangan Sekolah Teknologi Menengah - Sutrisno Sutrisno; Paryono Paryono (Universitas Negeri Malang, 2016)
The implementation of learning process in counterpart institutions should be taken into account, because the process is not managed by teacher bu by a business enterprise. The purpose of this study is to describe the expectation and implementation of the learning process, especially in selection of students, realization of instruction and evaluation, students' readiness, instructors' readiness, institutions' readiness, and pupil management. The sample consists of 59 students, 30 instructors, and 30 business enterprises from seven municipalities in East Java. Data are collected by questionnaire and analysed statistically in percentages and mean measures. The results reveal that selection of students is good, realization of instruction is good, evaluation is good, students' readiness and instructors' readiness are moderate, institutions' readiness is good, and pupil management is good